Hubble Space Telescope space astronomy images inspire art and enlighten humanity (TEST XY. Critical review of studies on the representation of architecture and use of the image in science and art, 2018)
For twenty seven years, the images taken by the Hubble Space Telescope have inspired artists all over the world. To scientists, they are a key tool in the pursuit of the fundamental questions: “Where do we come from?”, “Where are we going?”, “Are we alone?”. These questions are undoubtedly of great interest to professional astronomers, but they also hold profound meaning for every single person on Earth. This exhibition invites us to reflect on the theme of Our Place in Space. In the vastness of space, in the grand design of the Universe, where is humanity’s place? The artists taking part in this exhibition have been asked to give us their personal interpretations of famous Hubble images. Reflecting their own widely different experiences, they have addressed questions of where we are and where we belong, and also where we came from and where we might travel to in a hypothetical future.